Ultrafast lasers and optics for experimentalists - Pickering, James David (IOP (Series). Release 21., 2021)
The use of ultrafast lasers has expanded beyond use by specialist laser physicists and is increasingly commonplace in both physical and life sciences, where the high intensities, broad bandwidths, and short pulse durations make them ideal for investigating a wide range of chemical and physical phenomena. Working with these ultrashort femtosecond laser pulses requires some special care when compared to other laser systems, and this book provides an ideal starting point for the non-specialist to gain the necessary knowledge to start effectively working with ultrafast lasers and optics. The book walks the reader through the relevant parts of ultrashort pulse physics, pulse generation, and pulse characterisation, before discussing how to practically build an optical setup and manipulate these pulses. Many aspects of the practicalities of working with optics and lasers that are often considered assumed knowledge by experienced campaigners are discussed in detail. Aimed specifically at non-specialists, the emphasis is placed on intuitive, qualitative understanding of the concepts. The fundamental aim is that students starting a project or PhD in a laser group, can pick this book up and quickly get up to speed with the fundamentals of ultrafast laser physics that enable effective laboratory working.